2002
DOI: 10.1007/s00431-001-0891-7
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of octreotide in the treatment of post-operative chylothorax

Abstract: octreotide, a somatostatin analogue, may be effective in the treatment of post-operative chylothorax.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
27
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(29 citation statements)
references
References 10 publications
(23 reference statements)
2
27
0
Order By: Relevance
“…Several recent case reports and small institutional series have reported a 0022-3468/$ -see front matter D 2006 Elsevier Inc. All rights reserved. doi:10.1016/j.jpedsurg.2005.12.041 reduction in overall hospitalization as a result of hastened resolution of chylous effusions [4,7,8,11]. We report here the successful use of continuous administration of octreotide to treat congenital bilateral chylous effusions in a newborn.…”
mentioning
confidence: 78%
See 1 more Smart Citation
“…Several recent case reports and small institutional series have reported a 0022-3468/$ -see front matter D 2006 Elsevier Inc. All rights reserved. doi:10.1016/j.jpedsurg.2005.12.041 reduction in overall hospitalization as a result of hastened resolution of chylous effusions [4,7,8,11]. We report here the successful use of continuous administration of octreotide to treat congenital bilateral chylous effusions in a newborn.…”
mentioning
confidence: 78%
“…Prolonged chyle loss leads to loss of lymphocytes, protein, and immune globulins, placing the patient at risk for infection, malnutrition, and anasarca. Although most individuals respond to conservative therapy, surgical intervention such as thoracic duct ligation [7], pleuroperitoneal shunts [8][9][10], or pleurodesis is recommended after a 5 to 7 days course of medical therapy has failed [9].…”
mentioning
confidence: 99%
“…More than 90% shrinkage of lymphangioma was noted nutrition is often effective. Recently, successful treatment of postoperative chylothorax by octreotide has been reported [3,4]. It has been shown that somatostatin at a near physiologic dose reduces canine thoracic duct lymph flow rate.…”
Section: Discussionmentioning
confidence: 99%
“…Most reports describe its use following failure of conservative measures. In these reports lymphatic fistula output usually decreased dramatically within 72 h and essentially stops within 5-10 days [2,3,[15][16][17][18][19][20][21]. This dramatic response has prompted Leibovitch et al to recommend that it be used early in treatment of postoperative chylous ascites, prior to instituting TPN [22].…”
Section: Commentmentioning
confidence: 92%